Real-world effectiveness and safety of sacubitril/valsartan in heart failure: A systematic review. (15th May 2021) - Proudfoot, Clare; Studer, Rachel; Rajput, Tanvi; Jindal, Ramandeep; Agrawal, Rumjhum; Corda, Stefano; Senni, Michele
Abstract: Background: PARADIGM-HF demonstrated superiority of sacubitril/valsartan (sac/val) over enalapril in patients with heart failure with reduced ejection fraction (HFrEF). However, patients in clinical practice may differ in their characteristics and overall risk compared with patients in clinical trials, and additional outcomes can be observed in real world (RW). Hence, a systematic review was conducted to identify and describe RW data on sac/val. Methods: RW studies evaluating the effects of sac/val in adult patients with HFrEF with a sample size ≥100 were identified via MEDLINE® and Embase® from 2015 to January 2020. Citations were screened, critically appraised and relevant data were extracted. Results: A total of 68 unique studies were identified. Nearly half of the studies were conducted in Europe ( n  = 34), followed by the US ( n  = 15) and Asia ( n  = 11). Median follow-up period varied from 1 to 19 months. Mean age ranged between 48.7 and 79.0 years; patients were mostly male and in New York Heart Association (NYHA) functional class II/III, and mean left ventricular ejection fraction varied between 23%and 38%. Of studies performing comparisons, most reported superior efficacy of sac/val in reducing the risk of HF hospitalisations, all-cause hospitalisations, and all-cause mortality as compared to standard-of-care. Many studies reported significant improvements in NYHA functional class and reduction in biomarker levels post sac/val. Hypotension and hyperkalaemia were the most frequently reported adverse events. Conclusions: This comprehensive overview of currently available RW evidence on sac/val complements the evidence from randomised controlled trials, substantiating its effectiveness in heterogeneous real-world HF populations. Highlights: First systematic review of rich real world evidence base for sacubitril/valsartan. Effectiveness of sacubitril/valsartan from comparative observational studies. Data on real-world dosing, safety and benefits on biomarker and functional class. Evidence from real world complements conclusions from randomised controlled trials.